The gift of health promotion in a celebration: A descriptive observational study of community baby showers on YouTube - Aysha Jawed; Colin Gardiner (BioSocial Health Journal)
Introduction: Although community baby showers have persisted as a global health promotion practice for infants and their families over the past decades, to date there is no study that has evaluated coverage and engagement of community baby showers across social media as a rising global health communication medium in this contemporary digital era. It follows that the goal of this study sought to fill this gap by examining the existing state of coverage for community baby showers on social media utilizing view count as an engagement metric. Methods: In this cross-sectional, descriptive and observational study, we conducted a content analysis of the top 100 most widely viewed videos populated on YouTube at one conceptual point in time that covered community baby showers. to determine the most prevalent sources, formats, and content represented across this sample of videos. Results: Many of the videos were published by nongovernmental / organizational sources (n=86) and among them, the majority were in the form of news reports (n=59). Content across these videos presented a diversity of community stakeholders and entities involved in the development and implementation of community baby showers, many which were both for-profit and non-profit organizations (n=72). There was substantial coverage of a wide range of resources and services for prenatal and postnatal care delineated across all of the videos in this sample. Several videos (n=39) covered increased support building for families of infants. Notably, these videos cumulatively generated a low number of views (N=73,036) which yields clinical, educational, and public health implications. Conclusion: Recommendations to partner with news organizations and utilize content that generated greater viewership as facilitators in increasing capacity to reach, engagement and impact of community baby showers are presented to optimize infant health outcomes, reduce infant mortality, and heighten access to resources and support for infants and their families worldwide.